Pemanfaatan Minyak Esensial Bunga Sakura Dan Daun Teh Hijau Sebagai Parfum Di Desa Cihideung - Astuty, Meilinda Windy; Putra, Fani Pratama; Oktaviani, Dea Tri; Fauzah, Maida Fitria; Hamdani, M. Farhan; Gunawan, Salma Oktaviani (Pakis Journal Institute, 2025)
Perfume is a combination of essential oils and aromatic compounds used to impart a fragrant scent to the body, objects or a room. The use of perfume has a long history, dating back thousands of years, and was used by ancient civilizations in Egypt, Mesopotamia, and Greece as part of religious rituals and daily activities. This Community Service aims to introduce products made from natural ingredients to PKK mothers in Cihideung Village. This activity is expected to increase community knowledge about the utilization of natural materials and improve the economy through perfume production. A total of 20 PKK mothers from Cihideung Village participated in this activity. This service method was carried out through a field survey, followed by counseling which included lectures, discussions and question and answer sessions. In addition, the handover of “Raelda Perfume Products” was also carried out. It is hoped that the results of this activity can help participants in making perfumes and other natural-based products. The evaluation showed that this activity was useful and in accordance with the needs of the community.